﻿Checklist of the caddisflies (Insecta, Trichoptera) of the Upper Midwest region of the United States - David C. Houghton; R. Edward DeWalt; Todd Hubbard; Kurt L. Schmude; Jeffrey J. Dimick; Ralph W. Holzenthal; Roger J. Blahnik; James L. Snitgen (ZooKeys, 2022)
Five hundred and fifty-two caddisfly species are reported from the Upper Midwest region of the United States, an area that includes 13 states and ~ 2 million km2. Of these, 62 species are reported for the first time from the state of Iowa, 25 from Wisconsin, 18 from South Dakota, 12 from Illinois, five from Indiana, four from North Dakota, four from Minnesota, and one from Nebraska. The Upper Midwest fauna contains nearly 40% of all species known from the United States and Canada, as well as 22 species endemic to the region. Overall species richness was highest in Michigan (319 species), Kentucky (296), Minnesota (292), and Wisconsin (284). Differences in state species assemblages within the region largely followed a geographic pattern, with species richness declining in the western prairie states. There are almost certainly further species remaining to be found in this large region.